Human communication : - Tubbs, Stewart L. (McGraw-Hill, 2010)
Intended for the introductory communication concepts course, this text focuses on the principles and contexts of communication studies. The award-winning author links theory and research with fundamental concepts to create plentiful opportunities for students to apply their understanding and develop practical communication skills. His exposition is seasoned with intriguing case studies and stimulating examples drawn from contemporary life. In addition, Tubbs shows a true sensitivity to diversity--a reflection of his professional interests in gender and cultural issues.